Pelaksanaan Inklusi di Sekolah SDIT Rahmaniyah Depok - Imam Hasani; Hamam Thoriq Majid; Imran Revanza; George Khatami Albusthomi (Lembaga Pengembangan Kinerja Dosen, 2024)
Children with disabilities face increasing challenges due to society's negative views that limit their social and emotional development and cause many families to feel ashamed and hide them from important social interactions. Education is considered key to ensuring their rights, but exclusive education systems often limit their access with a lack of facilities and teacher training. Inclusive education was identified as a potential solution, allowing them to study in nearby schools without being restricted by special needs, increasing access to education and changing society's view of disability to promote social inclusion and equal rights.